Protocol for Past BP: a randomised controlled trial of different blood pressure targets for people with a history of stroke of transient ischaemic attack (TIA) in primary care. - Fletcher, K; Mant, J; Mcmanus, R; Campbell, S; Betts, J; Taylor, C; Virdee, S; Jowett, S; Martin, U; Greenfield, S; Ford, G; Freemantle, N; et al. (BioMed Central, 2010)
BACKGROUND: Blood pressure (BP) lowering in people who have had a stroke or transient ischaemic attack (TIA) leads to reduced risk of further stroke. However, it is not clear what the target BP should be, since intensification of therapy may lead to additional adverse effects. PAST BP will determine whether more intensive BP targets can be achieved in a primary care setting, and whether more intensive therapy is associated with adverse effects on quality of life. METHODS/DESIGN: This is a randomised controlled trial (RCT) in patients with a past history of stroke or TIA. Patients will be randomised to two groups and will either have their blood pressure (BP) lowered intensively to a target of 130 mmHg systolic, (or by 10 mmHg if the baseline systolic pressure is between 125 and 140 mmHg) compared to a standard group where the BP will be reduced to a target of 140 mmHg systolic. Patients will be managed by their practice at 1-3 month intervals depending on level of BP and followed-up by the research team at six monthly intervals for 12 months.610 patients will be recruited from approximately 50 general practices. The following exclusion criteria will be applied: systolic BP <125 mmHg at baseline, 3 or more anti-hypertensive agents, orthostatic hypotension, diabetes mellitus with microalbuminuria or other condition requiring a lower treatment target or terminal illness.The primary outcome will be change in systolic BP over twelve months. Secondary outcomes include quality of life, adverse events and cardiovascular events.In-depth interviews with 30 patients and 20 health care practitioners will be undertaken to investigate patient and healthcare professionals understanding and views of BP management. DISCUSSION: The results of this trial will inform whether intensive blood pressure targets can be achieved in people who have had a stroke or TIA in primary care, and help determine whether or not further research is required before recommending such targets for this population. TRIAL REGISTRATION: ISRCTN29062286.